Attenuation of Postharvest Browning in Rambutan Fruit by Melatonin Is Associated With Inhibition of Phenolics Oxidation and Reinforcement of Antioxidative Process - Wei, Dongling; Yang, Jiali; Xiang, Yue; Meng, Lanhuan; Pan, Yonggui; Zhang, Zhengke (Frontiers in Nutrition, 2022)
Rambutan is a famous tropical fruit with a unique flavor and considerable economic value. However, the high vulnerability to postharvest browning leads to a short shelf life of rambutan fruit. Melatonin (MT) is an excellent bioactive molecule that possesses the potential to improve the storability of the harvested crops. In this study, the physiological mechanism of exogenous MT in affecting pericarp browning and senescence of postharvest rambutan fruit was investigated. Experimental results showed that the application of MT at 0.125 mmol L–1 appreciably retarded the advancement of pericarp browning and color parameters (L*, a*, and b*). MT treatment inhibited the increase in membrane relative electrolytes leakage (REL) while lowering the accumulation of reactive oxygen species (ROS) (■O2– and H2O2) and malonaldehyde (MDA). Reduced phenolics oxidation, as indicated by higher contents of total phenolics, flavonoids, and anthocyanins along with fewer activities of peroxidase (POD) and polyphenol oxidase (PPO), was detected in MT fruit compared with control fruit. MT treatment maintained the cellular redox state by inducing antioxidant enzyme activity and reinforcing the ascorbate-glutathione (AsA-GSH) cycle. Furthermore, the ultrastructural observation revealed that the spoilage of cellular and subcellular structures was milder in MT fruit than that in control fruit. The results suggest that MT could ameliorate the browning and senescence of rambutan fruit by inhibiting phenolic oxidation and enhancing the antioxidative process.